Digital Psychosocial Follow-up for Childhood Critical Illness Survivors: A Qualitative Interview Study on Health Professionals’ Perspectives - Hagen Marte Hoff; Hartvigsen Gunnar; Jaccheri Letizia; Papavlasopoulou Sofia (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology)
Digital solutions have been reported to provide positive psychological and social outcomes to childhood critical illness survivors, a group with an increased risk for long-term adverse psychosocial effects.